2022
DOI: 10.1017/s003329172200294x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychological factors associated with resilience in patients with schizophrenia: data from the Italian network for research on psychoses using machine learning

Abstract: Background Resilience is defined as the ability to modify thoughts to cope with stressful events. Patients with schizophrenia (SCZ) having higher resilience (HR) levels show less severe symptoms and better real-life functioning. However, the clinical factors contributing to determine resilience levels in patients remain unclear. Thus, based on psychological, historical, clinical and environmental variables, we built a supervised machine learning algorithm to classify patients with HR or lower resilience (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
(131 reference statements)
0
0
0
Order By: Relevance
“…Although this association has been demonstrated in several studies, the speci c neural mechanisms are unclear. Previous studies have demonstrated that better sleep quality and higher resilience level are protective factors for NPS in LLD patients [25,53]. The protective effect of these factors was similarly demonstrated in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Although this association has been demonstrated in several studies, the speci c neural mechanisms are unclear. Previous studies have demonstrated that better sleep quality and higher resilience level are protective factors for NPS in LLD patients [25,53]. The protective effect of these factors was similarly demonstrated in our study.…”
Section: Discussionsupporting
confidence: 90%